A comparison of wintering in dry lot with wintering on dry bluestem pasture for yearling steers on a wintering, grazing, and fattening program. - Smith, E.F.; Koch, B.A.; Cox, R.F.; Walker, G.L. (Kansas Agricultural Experiment Station, 2011)
Yearling steers often are used by Kansas producers in a wintering, grazing, and fattening program or some variation of it. They can usually be purchased at a lower price per hundredweight than steer calves and may be finished with a relatively shorter feeding period in the late summer or fall. They consume large quantities of roughage, which may increase their feed cost considerably in the wintering phase. This study is concerned with lowering the cost of wintering and its effect on future performance, especially with respect to the effect on the carcass produced. The steers will be grazed on bluestem pasture until about July 1, When they will be started on a full feed of grain. They will be marketed when they reach the choice slaughter grade.
Keywords: Beef; Bluestem; Steers; Performance